By degrees : benchmarking archaeology degrees at Australian universities. - Clarke, Catherine (Australian Learning & Teaching Council, 2008)
This document is one outcome of a project, 'Benchmarking Archaeology Degrees in Australian Universities', which aimed to establish and develop mutually agreed standards for Honours degrees in archaeology in Australian universities. The benchmark contained in this document was drafted by a group representing all university providers of specialised archaeology education in Australia, and refined by consultation amongst the broader profession. It focuses on the four-year Honours degree in archaeology because this is considered to be the minimum preparation for both professional archaeologists and higher degree study. The benchmark defines the range of knowledge, skills and understandings Honours graduates in archaeology can be expected to possess, and outlines potential employment areas.